Competitive strategies in business - S, Sharma (Journal of Management and Science, 2020)
In a competitive strategy, the business has great value in recognizing the skills and businesses that need to attract customers and their comprehensive options to improve their position in the market. This concept distinguishes the "perspectives and actions" of managers from a strategic point of view. It means that the competitive strategy revolves around the pioneers' methods to improve the company's position in the market by satisfying customers. It Improves market conditions simultaneously leads to action against competitors. The competence of a competitive strategy (rather than a strong strategy) has a competitive impact. The competitive strategy involves techniques that follow different ways of managing the progress of the competition. The purpose of a competitive strategy is to win the hearts of competitors (or rival networks) by meeting customers' needs to achieve a competitive strategy. So, this article focuses on all aspects of competitive strategy in companies.